LightCue: An Innovative Far-Red Light Emitter for Locally Modifying the Spectral Cue in Outdoor Conditions with Global Consequences on Plant Architecture - Alain Fortineau (MDPI AG, 2021)
Plasticity of plant architecture is a promising lever to increase crop resilience to biotic and abiotic damage. Among the main drivers of its regulation are the spectral signals which occur via photomorphogenesis processes. In particular, branching, one of the yield components, is responsive to photosynthetic photon flux density (PPFD) and to red to far-red ratio (R:FR), both signals whose effects are tricky to decorrelate in the field. Here, we developed a device consisting of far-red light emitting diode (LED) rings. It can reduce the R:FR ratio to 0.14 in the vicinity of an organ without changing the PPFD in outdoor high irradiance fluctuating conditions, which is a breakthrough as LEDs have been mostly used in non-fluctuant controlled conditions at low irradiance over short periods of time. Applied at the base of rapeseed stems during the whole bolting-reproductive phase, LightCue induced an expected significant inhibitory effect on two basal targeted axillary buds and a strong unexpected stimulatory effect on the overall plant aerial architecture. It increased shoot/root ratio while not modifying the carbon balance. LightCue therefore represents a promising device for progress in the understanding of light signal regulation in the field.